Unveiling genetic signatures associated with resilience to neonatal diarrhea in lambs through two GWAS approaches - Yalçın Yaman; Yiğit Emir Kişi; Serkan S. Şengül; Yasin Yıldırım; Veysel BAY (Scientific Reports, 2024)
Abstract Neonatal diarrhea presents a significant global challenge due to its multifactorial etiology, resulting in high morbidity and mortality rates, and substantial economic losses. While molecular-level studies on genetic resilience/susceptibility to neonatal diarrhea in farm animals are scarce, prior observations indicate promising research directions. Thus, the present study utilizes two genome-wide association approaches, pKWmEB and MLM, to explore potential links between genetic variations in innate immunity and neonatal diarrhea in Karacabey Merino lambs. Analyzing 707 lambs, including 180 cases and 527 controls, revealed an overall prevalence rate of 25.5%. The pKWmEB analysis identified 13 significant SNPs exceeding the threshold of ≥ LOD 3. Moreover, MLM detected one SNP (s61781.1) in the SLC22A8 gene (p-value, 1.85eE-7), which was co-detected by both methods. A McNemar’s test was conducted as the final assessment to identify whether there are any major effective markers among the detected SNPs. Results indicate that four markers—oar3_OAR1_122352257, OAR17_77709936.1, oar3_OAR18_17278638, and s61781.1—have a substantial impact on neonatal diarrhea prevalence (odds ratio: 2.03 to 3.10; statistical power: 0.88 to 0.99). Therefore, we propose the annotated genes harboring three of the associated markers, TIAM1, YDJC, and SLC22A8, as candidate major genes for selective breeding against neonatal diarrhea.